Penerapan Origami Dalam Pembelajaran Prakarya di Sekolah Dasar - Wikarya, Rahmi Oktayory; Wikarya, Yusron; Fitryona, Nessya; Eswendi, Eswendi; Irwan, Irwan; Krisnanda, Shindu (ABDI HUMANIORA: Jurnal Pengabdian Masyarakat Bidang Humaniora, 2025)
Elementary school teachers encounter a range of challenges in fulfilling their professional responsibilities. These issues require systematic and gradual solutions. In collaboration with partner institutions, two priority areas were identified: (1) the conceptual development of origami as a craft lesson in elementary schools, and (2) the practical implementation of origami crafts in classroom. The problem-solving approach involved model development, counseling, and training activities. In line with the predetermined output targets, the program successfully produced several mandatory outputs: (1) scientific articles published in journals or proceedings, (2) articles disseminated through electronic media, and (3) short activity videos with a maximum duration of five minutes. Additional outputs included: (1) enhanced application of science and technology within the community through the integration of origami craft techniques at partner elementary schools, (2) improved community capacity reflected in increased knowledge and skills of participants, and (3) training products serving as methods, systems, or service-oriented innovations.